2019
DOI: 10.1002/adfm.201807104
|View full text |Cite|
|
Sign up to set email alerts
|

A Hybrid Nanovector of Suicide Gene Engineered Lentivirus Coated with Bioreducible Polyaminoglycosides for Enhancing Therapeutic Efficacy against Glioma

Abstract: An emerging hybrid nanovector integrating the merits of both viral and nonviral vectors has attracted much attention as the next generation of promising gene vectors to overcome the primary challenge of cancer gene therapy. Due to its inherent advantages, lentivirus (Lv) has been increasingly applied and investigated in medical fields. Herein, a new hybrid nanovector (SS‐HPT/Lv) composed of the Lv core and reduction‐responsive hyperbranched polyaminoglycoside (SS‐HPT) shell is designed via electrostatic intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…275 Recently, they reported, LVpolyaminoglycoside complexes, which efficiently induce cell apoptosis to glioma cells by facilitating cellular uptake via endocytosis pathways. 276 Polysaccharides are highly suitable biopolymers for viral gene delivery, mainly as hydrogels that adapt to the tissue environment. Release of VPs is achieved by degradation into non-toxic components.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…275 Recently, they reported, LVpolyaminoglycoside complexes, which efficiently induce cell apoptosis to glioma cells by facilitating cellular uptake via endocytosis pathways. 276 Polysaccharides are highly suitable biopolymers for viral gene delivery, mainly as hydrogels that adapt to the tissue environment. Release of VPs is achieved by degradation into non-toxic components.…”
Section: Biomaterials Science Reviewmentioning
confidence: 99%
“…In 2014, we also demonstrated that in animal models of human GSCs, an oncolytic HSV-1 that encodes an endostatin-angiostatin fusion gene could greatly enhance antitumor efficacy compared to HSV-1 without the fusion gene by generating antitumor angiogenic activity 21 . Later, our research team found that viruses that express the suicide gene cytosine deaminase (CD) could significantly enhance antitumor efficacy and prolong the life expectancy of tumor-bearing animals by the subsequent conversion of nontoxic prodrugs into toxic prodrugs 22,23 . Our research team independently developed a novel oHSV-1 containing the CD therapeutic gene.…”
Section: Introductionmentioning
confidence: 99%
“…(b) Representative T2WI images of intracranial tumors monitored by MRI on Day 5–24 after C6 cell implantation with different treatments. (Reprinted with permission from Fan et al (). Copyright 2019 Wiley‐VCH)…”
Section: Redox‐responsive Degradable Branched Polycationic Systemsmentioning
confidence: 99%
“…HDDE was acquired through the reaction of 2-hydroxyethyldisulfide and epichlorohydrin under alkaline conditions. According to Steinhilber's method, a series of redox-responsive ARP were prepared through amino-epoxy ring-opening reaction by using HDDE (Fan et al, 2019;Huang, Ding, Qi, Yu, & Xu, 2016). Such branched polycationic systems from HDDE demonstrated good redox-responsive degradability.…”
Section: Redox-responsive Degradable Branched Polycationic Systemsmentioning
confidence: 99%
See 1 more Smart Citation